Chiral Surface Lattice Resonances. Issue 22 (21st April 2020) - Goerlitzer, Eric S. A.; Mohammadi, Reza; Nechayev, Sergey; Volk, Kirsten; Rey, Marcel; Banzer, Peter; Karg, Matthias; Vogel, Nicolas
Abstract: Collective excitation of periodic arrays of metallic nanoparticles by coupling localized surface plasmon resonances to grazing diffraction orders leads to surface lattice resonances with narrow line width. These resonances may find numerous applications in optical sensing and information processing. Here, a new degree of freedom of surface lattice resonances is experimentally investigated by demonstrating handedness‐dependent excitation of surface lattice resonances in arrays of chiral plasmonic crescents. The self‐assembly of particles used as mask and modified colloidal lithography is applied to produce arrays of planar and 3D gold crescents over large areas. The excitation of surface lattice resonances as a function of the interparticle distance and the degree of order within the arrays is investigated. The chirality of the individual 3D crescents leads to the formation of chiral lattice modes, that is, surface lattice resonances that exhibit optical activity. Abstract : Surface lattice resonances result from coupling of localized surface plasmon resonances to grazing diffraction orders. By arranging chiral nanocrescents into periodic arrays with controlled interparticle distances, chiral lattice resonances become accessible. These resonances show a selective response to the handedness of incident circularly polarized light. Such arrays are fabricated over large areas (>cm 2 ) by self‐assembly of core–shell masking particles and modified colloidal lithography.